Injury risk factors for runners - Francisco Rodal Abal; José Luis García Soidán; Víctor Arufe Giráldez (FEADEF, 2013)
The purpose of this study was to determine those risk factors that may cause running injuries in general, and particularly damage to the muscle mass, and the tendon. Twenty six male and female Galician runners were evaluated about their lower limb flexibility and length, knee Q angle, explosive power and training features such as kilometers and sessions per week, level of competition, shoes, surface, injuries last year, use of insoles, athletic specially, age, weight and height. During next 12 weeks runners continued training as they had been doing regularly and we recorded all injuries that appeared in this period. After that and from the liner regression we obtained different models that explained the variability of general injuries, tendon injuries and damages to the muscle mass. We also find positive correlations between previous injuries and training volume, and these with the dependent variable «injuries in 12 weeks». In regard to tendinopathy and muscle mass injuries, we observed that the synthetic material present in the track is a risk factor for these muscle injuries. Meanwhile, the increasing age and the Q angle, increments the occurrence of tendon injuries.